CORPORA IN TEACHING ENGLISH LANGUAGE VOCABULARY (CORPUS-BASED L2 VOCABULARY TEACHING) - Abdunazar Kh. Juraev; Uktam D. Esanov; Jamila F.Rustamova; Komila F. Gulamjanova (Central Asian Journal of Medicine, 2023)
Efforts have been underwent in recent years to teach vocabulary in L2 in Uzbekistan. This is due to the development of new "word-based" approaches to L2 training, the inclusion in the Internet database of language Corps, which includes thousands of dictionaries used in real texts. To teach L2 vocabulary, a language corpora can also be used as invaluable sources of various activities. What should teachers do to make it easier for their students to master new words? This article aims to answer this question by giving examples of a number of tutorials that show how vocabulary training in the L2 class can be done effectively and attractively, using language Corpus, with concorandans programs. The first part of this article provides theoretical information on the processing, storage and production of new words, and the second part provides educational tasks that help memorize the dictionary. The final section of this article shows how to teach students how to overcome vocabulary deficits.